Types of Innovation and State Support in the Field of European Creative Territories: A Literature Review - Bozhikin, Ivan (Research Papers, 2024)
Creative territories are one of the current topics that have attracted the attention of researchers in the last decade. Some of the research in this scientific area focuses on cultural heritage, and others on the economy and creative industries, including smart and creative cities. The present research aims to discover the different innovations in the European creative territories and the governmental regulatory mechanisms to stimulate them. To achieve this goal, a systematic literature review was conducted. The following two research questions were formulated: Q1: What are the key innovations created in European creative territories? Q2: What are the main regulatory mechanisms of European governments for the development of European creative territories? As a result of the research, 11 innovations created in the European creative territories and 7 regulatory mechanisms to stimulate these territories are indicated. A brief conclusion is presented at the end of the development.